The effectiveness of a reprocessing protocol in the sterilization of a high speed hand pieces in a gravitational autoclave - Alvarenga, Camila Fonseca (2011)
High rotation pen are instruments used a lot on dentistry clinical practice over polemic decontamination because its complex functioning. Microbiologic study conducted in the Dental Clinic of the Federal University of Goias, which aimed to evaluate effectiveness-reprocessing protocol of high rotation pen in a gravity-autoclave based on a protocol. All ethical aspects were observed and the data were obtained by microbiological analysis, information from medical records and questionnaire to dentists. After its use the pens were reprocessed and sent to the laboratory for microbiological collection. Samples of six pens used in 60 different patients were collected based on the reprocessing protocol. Swabs moistened in saline solution were swabbed inside the head pen’s walls and transferred to a sodium thioglycollate solution and incubated for seven days at 37ºC. The 60 samples showed no microbial growth, demonstrating the effectiveness of sterilization in gravitational autoclaves based on reprocessing protocol. Descriptors: Sterilization; Dental instruments; Infection control.